Virtual nature makes knowledge beautiful - Harrington, Maria C. R. (Frontiers in Virtual Reality, 2023)
This is a perspective that presents a viewpoint on immersive informal learning applications built as digital twins of the natural world. Such applications provide multimodal, interactive, immersive, embodied, and sensory experiences unique and different from typical game art environments because they are geospatial visualizations of data and information derived from ecological field plot studies, geographical information systems, drone images, and botanically correct 3D plant models visualized in real-time interactive game engines. Since they are constructed from geometric objects, they can programmatically self-express semantic data and connect to knowledge stores on the Internet to create a web of knowledge for both exploration of a virtual environment as a natural landscape and for exploration of connected knowledge stores for informal learning at the moment of curiosity. This design is exceptionally powerful for informal learning as it supports the innate human desire to understand the world. This paper summarizes the construction methods used for creating three digital twins of natural environments and the informal learning applications created and distributed, namely, augmented reality (AR), virtual reality (VR), and virtual field trips. Informal learning outcomes and emotional reactions are evaluated using mixed-methods research studies to understand the impact of design factors. Visual fidelity and navigational freedom are combined to increase learning outcomes and many effective and emotional outcomes as well. Access to facts and story increase learning outcomes, and applications evaluated as beautiful are correlated with emotional reactions of awe and wonder, and awe and wonder are correlated with higher learning gains. Beauty is correlated with other system-wide subjective evaluations largely accepted as important to create a context conducive to support learning outcomes, such as calmness, excitement, and curiosity, a desire to share, and a desire to create. This paper summarizes the highlights of the author’s prior work to give the reader a perspective on the body of work.